Effect of different levels of social isolation on the acoustical characteristics of sheep vocalization - Engeldal SEC; Subandriyo .; Handiwirawan E; Noor RR (Jurnal Ilmu Ternak dan Veteriner, 2013)
In farm animals, vocal analysis is accepted as a non-invasive method for assessing animal welfare in comparison to most physiological measurements. The aim of this study was to investigate the influence of different degrees of social isolation on the acoustic characteristics of stress-induced bleats from three different breeds of sheep. The experiment consisted of subjecting the animals to three different levels of social isolation during which both locomotive and vocal data were recorded. The data on locomotive behaviour was subjected to descriptive analysis while specialized acoustic software was used to measure a total of thirty-six parameters of recorded bleats. Descriptive analysis showed that the animals displayed more locomotive activity during partial isolation compared to complete isolation. Number of bleats during partial isolation was also found to be higher. The application of two-way analysis of variance showed a significant effect of isolation level and breed on both temporal and structural acoustic properties. Amplitude, power and time acoustic properties were found to affect acoustic quality of vocal responses to isolation, whereas frequency related properties were also found to be different significantly (P < 0.05) between breeds. From spectrogram analysis, the patterns of energy distribution within the calls proved to offer the most evident that differ between isolation levels and breeds. It was concluded that acoustic analysis can be helpful in revealing the affective state of socially isolated rams. Key Words: Sheep, Social Isolation, Vocalization, Behaviour, Animal Welfare